Dampak Pelatihan Manajemen Kreatif Industri Peci Menuju Sentra Peci Di Desa Langonsari Kecamatan Pameungpeuk Kabupaten Bandung - Sambas Putra, Ivan Gumilar; Daniel Nababan; Andhika Ligar (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2020)
This study aims to determine the impact of the Peci industry's creative management training towards the Peci center in Langonsari Village, Pameungpeuk District, Bandung Regency specifically in the field of creative economy management. The study was conducted for 6 months in Langonsari Village, Pameungpeuk, Bandung. Data collection techniques using interviews, documentation, and observation with research subjects, namely the Village Head, BUMDES Manager, Mitra Peci Harmoni and some Desa Langonsari users of BUMDES services. In order to guarantee the validity of the data, researchers used source triangulation techniques. Data analysis in this study uses an interactive analysis model that is analysis using data reduction, data display, and verification and conclusions, the results of this study indicate that the creative management training for the peci industry to the peci center has succeeded in having a positive impact on improving the economy of the community.